The use of additives to enhance properties of pre-formed foamed concrete - Hilal, Ameer Abdulrahman; Thom, Nicholas; Dawson, Andrew (IACSIT Press, 2015)
This paper describes an experimental study of an enhancement of pre-formed foamed concrete, 1300-1900 kg/m3, by utilising two types of additives, silica fume and fly ash, to partially replace Portland cement and fine sand. It focuses on consistency, mechanical and thermal properties as well as presenting a comparison with normal weight, lightweight and foamed concretes from the literature. In addition to conventional foamed concrete mixes (FC), foamed concrete mixes with high flowability and strength (FCa) were also manufactured in this study. The FC mixes had 28-day compressive strengths from 6 to 23 MPa and corresponding thermal conductivities in the dry state from 0.475 to 0.951 W/mK, whereas for the same density range, the FCa mixes gave 19-47 MPa and 0.498-0.962 W/mK, respectively. Compared to other studies on foamed concrete, the results from the mixes investigated in this study showed higher strengths (for a given density), higher tensile to compressive strength ratios and higher moduli of elasticity.